MEASURING THE COMMUNICATION EFFECTS OF SALES PROMOTION IN A FOOD COMPANY - Mesaroš, Ines; Đokić, Nenad; Penić, Mirjana (Economics of Agriculture, 2013)
Consumer targeted sales promotion activities, especially discounts and complimentary products, are frequently pursued in food industry. Their fundamental goal is to boost sales over a given period, with short-term effects. However, studying literature dealing with effects of sales promotion, one will find controversies not only concerning expected economic effects of sales promotion, but also regarding unexpected economic impact of sales promotion on brand image, which is the communication goal of promotion itself. If some of the brand damage effects suggested in one part of literature were accepted as possible, this would result in adverse effect of sales promotion in comparison to other marketing communication tools. All of the above warns of the need to very carefully plan sales promotion activities undertaken by a food company, which requires the possibility of measuring communication effects of sales promotion. This article presents a method of measuring communication effects of sales promotion using the metric conjoint analysis technique on the example of a dairy product.